2009
DOI: 10.1590/s1517-86922009000600002
|View full text |Cite
|
Sign up to set email alerts
|

Influência do treino fisico moderado sobre a estrutura da parede arterial de ratos submetidos à desnutrição proteica gestacional e neonatal

Abstract: Avaliamos o efeito do treinamento físico moderado (TFM) associado à reposição nutricional na parede das artérias carótida comum esquerda e aorta horizontal em 24 ratos Wistar machos adultos jovens, submetidos à desnutição proteica nas fases gestacional e neonatal. Os animais foram divididos em grupos Nutrido (N, n = 12, caseína 17%) e Desnutrido (D, n = 12, caseína 8%). Após o desmame, todos os animais receberam dieta padrão (Labina®) e aos 60 dias de vida, os dois grupos foram subdivididos em quatro com seis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Similar data have been demonstrated by Maux et al (25) using the left common carotid artery of malnourished rats in the gestational and neonatal phases with hypoprotein diet which performed swimming training during eight weeks. On the other hand, the study by Tanaka et al (37) did not demonstrate differences in the thickness of the arterial wall of the common carotid in young (18-37 years), adults (38-57 years) and older (58-77 years) sedentary individuals and who have practiced regular physical training for three months.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar data have been demonstrated by Maux et al (25) using the left common carotid artery of malnourished rats in the gestational and neonatal phases with hypoprotein diet which performed swimming training during eight weeks. On the other hand, the study by Tanaka et al (37) did not demonstrate differences in the thickness of the arterial wall of the common carotid in young (18-37 years), adults (38-57 years) and older (58-77 years) sedentary individuals and who have practiced regular physical training for three months.…”
Section: Discussionsupporting
confidence: 86%
“…However, this same author in another study (24) , observed increase of thickness of arterial wall of the abdominal aorta in neonatal pups, attributing this divergence in results to the different models of fetal malnutrition. In addition to this, a previous study carried out in our laboratory in rats with 80 days of life whose mothers were fed with hypoprotein diet during the gestational and neonatal periods, demonstrated reduction of thickness of the left common carotid artery (25) . It has also been demonstrated that in humans and adults (mean of 58 years) whose mothers were not fed with hypoprotein diet presented reduction of thickness of the left common carotid artery (26) .…”
Section: Methodsmentioning
confidence: 52%
See 2 more Smart Citations